A tribute to José Manuel Valença - Oliveira, José Nuno; Pinto, Jorge Sousa; Barbosa, Luís Soares; Henriques, Pedro Rangel (Journal of logical and algebraic methods in programming, 2022)
The present Special Issue of the Journal of Logical and Algebraic Methods in Programming was planned as a tribute to José Manuel Esgalhado Valença on the occasion of his Jubilation. A tribute to a professor, in the deepest sense of the word, a colleague and a friend, but above all to a long and inspiring academic journey that has so profoundly shaped the development of Informatics as a scientific area in Portugal. A scientific area that, as he taught us, needs to be understood broadly: not only as an independent research domain, but also as an educational pillar, a strategy for social and economic development, a foundation for a multifaceted professional career. This preface introduces some steps of such a journey. The Special Issue features a selection of scientific papers written by his collaborators, colleagues and friends, covering the different areas José Valença helped to launch and consolidate in Portugal, namely computational logic, verification and mechanized reasoning, and information security.